Towards better blood transfusion--recruitment and training. - Hill, Q; Hill, A; Allard, S; Murphy, M (2009)
Recent national initiatives in blood transfusion safety in the UK have created the need for an expansion in haematologists subspecializing (wholly or in part) in transfusion medicine. In 2008, there are 62 transfusion consultants in the UK, but only 42 are full time, and only 19 have hospital sessions. Despite the need for expansion, recruitment appears difficult. The English blood transfusion service, National Health Service Blood and Transplant (NHSBT), is undergoing major reconfiguration, and the current practice of transfusion training for haematology specialists primarily at blood centres with little or no hospital training is not sustainable or desirable. Delivering a high-quality transfusion programme to haematology trainees is best achieved through an increased emphasis on hospital-based training. Improved research opportunities, joint NHSBT/hospital posts and a separate subspecialty training curriculum may stimulate interest in transfusion medicine.